Assessing organizational citizenship behaviour through constructing emotional intelligence - Anwar, Md. Aftab; Gani, Aahad M. Osman; Fontaine, Rodrigue Ancelot Harvey; Rahman, Muhammad Sabbir (Emerald Group Publishing Ltd., 2017)
Purpose – The purpose of this paper is to identify the relationships of the dimensions of emotional intelligence (EI) with organizational citizenship behaviour (OCB). EI is the capacity to recognise and articulate emotions among the individuals and others in the workplace. Emotional capabilities can be used to enhance a person’s ability in this particular field who can exhibit better OCB. Design/methodology/approach – This paper investigates the relationships of EI and its components with OCB among the employees who are working in the commercial banks of Malaysia. Data were collected from 293 employees from ten commercial banks operating in Peninsular Malaysia. Findings – Structural equation modelling approach was applied to this study and identified that employee EI plays a major role for enhancing their citizenship behaviour in the organization. The three components of EI, namely, use of emotion, others emotion appraisal, and regulation of emotion are having great effect on OCB. Research limitations/implications – Scholars can develop new research agenda to identify the nature of effects it might have on employee’s performance that can boost the ultimate goal of the organization. Practical implications – The empirical evidences from the findings of this study can contribute to advancing the current knowledge in the fields of organizational management and industrial sector by showing the differentiating effects of the dimensions of EI on OCB. Social implications – This study has the capacity to enhance management awareness concerning recruiting people in terms of EI. People from different culture with high level of citizenship behaviour can able to get the job. Originality/value – Findings from this study may create awareness and interests about the significance of conducting more research on EI and OCB by incorporating other variables/constructs of interests. Through the findings of this empirical study, it is confirmed that this research has provided some assessment and developed new knowledge about the effects of employees’ EI and how they relate this to their OCB.